Financing of smart and sustainable city projects - Filho, Luiz Orsatti; Cortese, Tatiana Tucunduva Philippi (Revista Nacional de Gerenciamento de Cidades, 2020)
The availability of financial resources is an indispensable requirement for the execution of any type of project, whether in Brazil or abroad, short or long term, public or private, and regardless of the area of human knowledge. The implementation of smart and sustainable city projects is complex and intersects and is more complicated due to the large financial volumes involved and the scarcity of public budget. Through integrative review of the literature, this article aims to research the issue of financing smart and sustainable city projects in Brazil and abroad, giving an overview of the current situation and emphasizing alternatives for increasing resources and expanding funding sources. The results showed that, even with all the concern and prestige of being elected one of the 17 Sustainable Development Goals by the UN, the implementation of smart and sustainable cities, through projects and actions, however relevant, efficient, modern, necessary, and beneficial to society, if they do not overcome the obstacle of financing, will not extend beyond ideas, with developing countries being the most affected. However, there was a range of initiatives that seek alternative financing, aiming to overcome the scarcity of resources and the need for implementation of such projects, but still require attention and improvement, and the so-called "sustainable financing" as a paradigm shift in investments, with great potential for growth and diversity of possibilities.